Respostas

A melhor resposta!
2013-06-19T15:07:59-03:00

é so juntar os termos semelhantes

a)3x - 7 = 9 - 5x

 3x+5x=9+7

 8x=16

 x=16/8

 x=2

 

nessa é bhaskara (eu acho)

 

b)-x² -2x+1=0

                                                                               

a=-1           =(-2)^{2}-4.1.(-1)             x=\frac{2+ou -\sqrt{8}}{2}

b=-2          =4+4                                                    

c=1            =8   

 

 

                                             ai é so termina:

 

                                            x1=\frac{2+8}{2}       ou              x2=\frac{2-8}{2}

                                            x1=\frac{10}{2}                            x2=\frac{-6}{2}

                                           x1=5                                                             x2=-3

2 5 2